KẾT QUẢ NGHIÊN CỨU CẤU TRÚC VỎ TRÁI ĐẤT BẰNG TÀI LIỆU SÓNG KHÚC XẠ CỦA HAI TUYẾN ĐỊA CHẤN DÒ SÂU Ở MIỀN BẮC VIỆT NAM - Toàn, Đinh Văn; Harder, Steven; Bắc, Trịnh Việt; Tuyến, Đoàn Văn; Phòng, Lại Hợp; Vũ, Trần Anh; Quang, Nguyễn Thị Hồng (Vietnam Journal of Earth Sciences, 2012)
The study of the crustal structures by using the seismic refraction data collected along the two profiles of deep seismic investigations in northern Vietnam Deep seismic sounding is the best tool for delineating the structures of the Earth’s crust and upper mantle. Limited research budget and dense population prevent to apply the techniques for the investigations. Since that, for the past about 40 years, the studies of the Earth’s crustal structures in Vietnam were carried out mainly based on the gravity data analysis. Just only in framework of the Vietnam National Project: KC.08.06/06-10, based on the cooperation between the Institute of Geological Siences and J. W. Miller Geophysical Laboratory, University of Texas at El Paso, USA, the first deep seismic experiment was carried out in northern VietNam. The two profiles with more than 120km long of each are intersected mostly the main tectonic units in the region. Each of these profiles consisted of six shots at three locations with the relatively small capacity of explosion from 550 to more than 1000kg. A total of 12 shots were fired into 200 Texan seismographs distributed along each profile with nominal interval of 500-700m. High noise level due to the waves recorded at daytime may suppressed the interested signals. Two types of seismic wave: reflection and refraction were observed on the wave sections obtained from the data processing. Just a half of the reflection sections allowed us to detect the signals related to full three main interfaces of the earth crust: Crystaline, Conrad and Moho. The remain reflection sections can observe the reflection signals in term of direct wave in a limited distance (30-35km) from the shot point. Fortunately the refraction signals are demonstrated more clearly than the reflection along whole profiles. This paper present the refraction wave sections obtained from processing data as well as the study of the crustal structures under the two profiles by using the techniques for travel time inversion. The analysis results provided more reliable data about the crustal structures under the investigated profiles and can be accepted as a standard model for interpretation of other geophysical data to improve the structures of the crust of northern Vietnam.